Challenges and Strategic Approaches in SME Internationalization: A Literature Review - Fetty Kwartati; Haris Maupa; Hadi Cahyadi (Proceeding of The International Conference on Business and Economics, 2024)
This paper explores the challenges and strategic approaches in the internationalization of small and medium-sized enterprises (SMEs). By conducting a systematic review of key literature, the study identifies three main challenges: resource constraints, regulatory and compliance barriers, and risk management. These obstacles significantly impact SMEs' ability to expand globally. However, the review also highlights strategic approaches that can help SMEs mitigate these challenges, including forming strategic alliances, adopting digital technologies, and diversifying leadership teams with international expertise. The findings suggest that SMEs must integrate market knowledge, local networks, and technology to enhance their international competitiveness. The paper offers practical recommendations for SMEs and policymakers to facilitate smoother international expansion.